U UPAYA PENINGKATAN PENGETAHUAN KESEHATAN TENTANG BAHAYA HIPERTENSI PADA LANSIA: Hipertensi, lansia, pengetahuan - Evi Vestabilivy; Rina Veronica (EDUPEDIA Publisher, 2023)
Hypertension is one of the most common cardiovascular diseases and is widely carried by the community. Hypertension is found in approximately 6% of the entire world population. Epidemiological data show an increase in the prevalence of hypertension, with increasing life expectancy or an aging population. The purpose of this community service is to socialize hypertension control to the wider community so that the development of this disease can be suppressed. This activity needs to be done considering the number of people with hypertension is increasing day by day. From the results of a survey conducted on residents of RT 4 RW 3, Jatiasih, Bekasi, there are quite a number of them. By doing this socialization/counseling it is hoped that people's knowledge about hypertension will increase, so that the risk factors for this disease will decrease and the quality of life of sufferers will increase.